Trees, soils, and warthogs - distribution of services and disservices from reforestation areas in southern Ethiopia - Byg, A.; Novo, P.; Dinato, M.; Moges, A.; Tefera, T.; Balana, Bedru; Woldeamanuel, T.; Black, H. (Elsevier, 2017)
Conservation projects have often been criticised for creating global benefits while causing negative impacts on local livelihoods. Ecosystem services approaches have been seen as one way to change this by focussing explicitly on maintaining ecosystems for human well-being of stakeholders at various scales. However, ecosystem services approaches have often ignored trade-offs between groups of people and issues of power and do not automatically lead to better outcomes in terms of human well-being. Here we report on a study on the impacts of reforestation projects with an explicit focus on human well-being in three communities in southern Ethiopia. We investigated the distribution of services and disservices from reforestation using qualitative methods. Results showed that the services and disservices from reforestation were distributed unequally across space and wealth groups resulting in widespread dissatisfaction with existing reforestation projects despite the explicit focus on human benefits. To improve outcomes of reforestation it is necessary to acknowledge and manage disservices adaptively, include issues of power and make trade-offs transparent.